Characterization of genetic polymorphisms in Toll-like receptor 9 gene of Bos indicus Sahiwal cattle - BEHL, JYOTSNA DHINGRA; SHARMA, ANURODH; KATARIA, R S; VERMA, N K; KIMOTHI, SHIV PRASAD; BHATIA, AVNISH KUMAR; BEHL, RAHUL (The Indian Journal of Animal Sciences, 2017)
Toll-like receptor 9 protein, located in the endosomal compartment, is a nucleotide-sensing Toll-like receptor(TLR). It is activated by unmethylated cytidine-phosphate-guanosine dinucleotides (CpG ODN) in both viruses and bacteria, and is encoded by Toll-like receptor 9 gene, which was sequenced and characterized in the Bos indicus Sahiwal cattle breed. Eleven single nucleotide polymorphisms (SNPs) were detected within the 4.8 Kb region of the TLR9 gene. Eight of the SNPs were present in the coding region of the gene and the other 3 were present in the non-coding part of the gene. The SNP 2930(G>A) was non-synonymous leading to an amino acid change of G437E in the TLR9 protein. The other SNPs were synonymous. These SNPs led to generation of 11 most probable TLR9 gene haplotypes. The gene exhibited a nonsignificant value of Tajima's D which indicated it to be following the neutral mutation hypothesis.